Pengaruh Current Ratio, Debt To Equity Ratio, Return On Equity dan Net Profit Margin terhadap Harga Saham pada Sub Sektor Food and Beverage yang Terdaftar di BEI Periode 2022-2024 - Eky Aulia Fitri; Hamida Sari Siregar (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study was motivated by the importance of financial performance indicators in influencing stock prices in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Investors generally use financial ratios as a basis for evaluating company performance and making investment decisions. Therefore, this study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Net Profit Margin (NPM) on stock prices. This research employed a quantitative approach with an associative research method. The population consisted of 51 Food and Beverage sub-sector companies listed on the IDX during the 2022–2024 period. The sample was selected using purposive sampling based on specific criteria, resulting in 13 companies with a total of 39 financial statement data observations. The data were processed using SPSS version 27 and analyzed through multiple linear regression analysis. The results indicate that CR, DER, ROE, and NPM collectively influence stock prices in the Food and Beverage sub-sector. However, only ROE shows a significant positive effect on stock prices, while CR, DER, and NPM do not have significant partial effects. These findings suggest that profitability, particularly ROE, plays a more dominant role in determining stock prices compared to liquidity and solvency factors during the 2022–2024 period in Indonesia.